MYTHS OF THE GREEN COUNTRY: THE ESSENTIAL BICENTENNIAL COSTA RICA - Cartagena Núñez, Catalina (2022)
This article analyzes the set of historical and sociocultural factors that have influenced the production of imaginaries about Costa Rica as the green country. For this, first we approach the social and political context in which the so-called “green myth” is established. Secondly, we deep dive into the representations of the natural landscape used in some advertising campaigns by Essential Costa Rica. Finally, we place side to side the imaginaries of the green exceptionality with the socio-environmental reality of the country. Based on this analysis, we intend to show some of the mechanisms by which these imaginaries produce ways of being and thinking about the country while erasing and making others invisible.